Alzheimer Amyloid-β Oligomer Bound to Post-Synaptic Prion Protein Activates Fyn to Impair Neurons - Um, Ji Won (2012)
Amyloid-beta (Aβ) oligomers are thought to trigger Alzheimer’s disease (AD) pathophysiology. Cellular Prion Protein (PrP(C)) selectively binds oligomeric Aβ and can mediate AD-related phenotypes. Here, we examined the specificity, distribution and signaling from Aβ/PrP complexes, seeking to explain how they might alter the function of NMDA receptors in neurons. PrP(C) is enriched in post-synaptic densities, and Aβ/PrP(C) interaction leads to Fyn kinase activation. Soluble Aβ assemblies derived from human AD brain interact with PrP(C) to activate Fyn. Aβ engagement of PrP(C)/Fyn signaling yields phosphorylation of the NR2B subunit of NMDA-receptors, which is coupled to an initial increase and then loss of surface NMDA-receptors. Aβ-induced LDH release and dendritic spine loss require both PrP(C) and Fyn, and human familial AD transgene-induced convulsive seizures do not occur in mice lacking PrP(C). These results delineate an Aβ oligomer signal transduction pathway requiring PrP(C) and Fyn to alter synaptic function with relevance to AD.